Ceria and Ce0.95M0.05O2 − δ mixed oxides (M = La, Pr, Zr): Vacancies and reducibility study - Iglesias, Ignacio Daniel (2017)
Highly reducible and redox active mixed oxides are employed in selective oxidation reactions and fuel cells, among others. Ceria is a renowned material in these applications because of its capacity to take and release oxygen. At the same time, these properties may be enhanced by cerium substitution with certain elements, usually, other rare earths. In this line, the present work is focused on the preparation of pure cerium oxide and doped with 5 %at of La, Pr or Zr. The solids were calcined at 600, 750 and 900 °C and characterized by diverse techniques (DRX, BET, Raman, OSC-OSCC, H2-TPR). When increasing calcination temperature, it was observed an improved specific surface and crystallite diameter conservation for La and Zr-doped samples. Oxygen vacancy generated by doping, observed both by Raman and OSC-OSCC, decreased with higher calcination temperatures for every solid. Ce0.95Pr0.05O2 − δ showed a maximum oxygen storage capacity for 750 °C calcination temperature consistent with Raman spectroscopy and hydrogen reduction profiles.